The writing centre as a Third Space in higher education: An autoethnographic reflection - Nendauni, L. (South African Journal of Higher Education, 2026)
Writing centres in higher education are often perceived as remedial spaces, yet they play a far more complex role in supporting student learning and shaping professional identities. In this article, I use autoethnography to explore how writing centres function as Third Spaces that blur the boundaries between teaching, academic development, and student support. Drawing on Third Space Theory and Academic Literacies Theory, I critically reflect on my experiences as a writing centre practitioner, examining the institutional positioning of writing centres and the evolving identities of those who work within these spaces. Despite contributing significantly to academic literacy development, writing centre practitioners remain in liminal professional spaces, often caught between academic and administrative roles. Through this reflection, I highlight how writing centres challenge deficit-based institutional narratives and foster student agency beyond the classroom. I propose that universities should move beyond the service-based model of writing centres and recognise them as intellectual spaces that play a critical role in academic development. I argue that through formally acknowledging writing centre practitioners as Third Space professionals, institutions can enhance their legitimacy and impact, strengthening their role in fostering inclusive, student-centred approaches to academic literacy.